The urban geography of boxing : race, class, and gender in the ring - Heiskanen, Benita. (Routledge research in sport, culture and society ;, 2012)
"This book is an interdisciplinary cultural examination of twenty-first century boxing as a professional sport, a bodily labor, a lucrative business, a popular entertainment, and an instrument of ideology. Based on ethnographic fieldwork and interviews conducted with Latino boxers, women boxers, and boxing insiders in Texas, it discusses boxing from the vantage point of the sundry players, who are involved with it: the labor force, promoters, handlers, ringside officials, medical professionals, media, and the audiences. The various parties have multiple stakes in the sport. For some, boxing is about physical empowerment; others are in it for the money; some deploy it for ideological purposes; yet others use it to claim their 15-minutes of fame, and frequently the various interests overlap. In this book, Benita Heiskanen makes a broader connection between boxing and the spatial organization of racialized, class-based, and gendered bodies within particular urban geographies. Journeying actual sites where the sport is organized, such as the barrio, boxing gym, and competition venues, she maps the ways in which boxing insiders negotiate a variety of conflicting agendas at local, regional, and national scales. Beyond the United States, the worker-athletes conduct their labor within global socioeconomic conditions, business networks, and legal principles. Through this sporting context, Heiskanens discussion discloses some complex socio-historical, cultural, and political power relations between urban margins and centers, with ramifications far beyond boxing. This book will be of interest to readers in Sport Studies, Cultural Studies, Cultural Geography, Gender Studies, Critical Race Theory, Labor Studies, and American Studies"--